PENGARUH CUSTOMIZATION, BASIC MARKET ORIENTATION, DAN COMPETITIVE BENCHMARKING TERHADAP CUSTOMER RETENTION USAHA KECIL GETUK GORENG SOKARAJA DI KABUPATEN BANYUMAS - Zulaicha, Ratni; Yunanto, Ary (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
The research was carried out on small business Getuk Goreng in Banyumas joined in union employers Getuk Goreng. This research will assist employers Getuk Goreng developing paradigm customer retention in variable customization, basic market orientation and competitive benchmarking to enable them to improve their performance in the face of competition.